2017
DOI: 10.1111/bcp.13319
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Safety Assessment 2016: Delivery of a national prescribing assessment to 7343 UK final‐year medical students

Abstract: AIMSNewly graduated doctors write a large proportion of prescriptions in UK hospitals but recent studies have shown that they frequently make prescribing errors. The prescribing safety assessment (PSA) has been developed as an assessment of competence in relation to prescribing and supervising the use of medicines. This report describes the delivery of the PSA to all UK final-year medical students in 2016 (PSA2016). METHODSThe PSA is a 2-hour online assessment comprising eight sections which cover various aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 19 publications
0
56
0
Order By: Relevance
“…Second, one recent important study was not included because the search was terminated before its publication. The latter study describes the delivery of a national prescribing assessment to 7343 UK final‐year medical students in 2016 98. Although there was significant variation in performance between final‐year medical students studying in different UK medical schools, their overall performance was good (95% passed the test).…”
Section: Discussionmentioning
confidence: 99%
“…Second, one recent important study was not included because the search was terminated before its publication. The latter study describes the delivery of a national prescribing assessment to 7343 UK final‐year medical students in 2016 98. Although there was significant variation in performance between final‐year medical students studying in different UK medical schools, their overall performance was good (95% passed the test).…”
Section: Discussionmentioning
confidence: 99%
“…Passing the PSA is now an essential part of successful completion of the foundation training year for newly qualified doctors. The vast majority of medical students, by preparing for and undertaking this assessment, have now been found to meet a pre‐specified standard of prescribing competence before entering clinical practice …”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of medical students, by preparing for and undertaking this assessment, have now been found to meet a pre-specified standard of prescribing competence before entering clinical practice. [10] Pharmacists constitute a significant part of the NHS workforce and are highly trained in all aspects of medicines use. Currently, the route to registration as a pharmacist involves completion of a General Pharmaceutical Council (GPhC) accredited 4-year MPharm degree and 1 year of pre-registration training or a 5-year MPharm degree with integrated pre-registration training, followed by successful completion of the GPhC's registration assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing literatures on internship are about medical students, especially those majoring in nursing. This is determined by the nature of this major, as medicine is all about saving lives and it cannot afford trial and error (Brinkman, Tichelaar, van Agtmael et al, 2015;Maxwell, Coleman, Bollington et al, 2017;Silva, Lopes, Costa et al, 2018). There are also many researchers who have discussed the internships of university students majoring in business and economics and concluded that these internships have a significant role in promoting the general abilities of graduates (Gault, Redington, & Schlager, 2000;Knouse & Fontenot, 2008;Schworm, Cadin, Carbone et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%